MENAKAR KEKUATAN KUALITAS PRODUK, CITRA MEREK, DAN BRAND PRESTIGE MEMICU MINAT BELI ULANG (Studi Empirik Produk Smartphone OPPO) - Morryessa Brandinie (Jurnal Ekonomi Perusahaan, 2017)
The purpose of this study is to measure the strength of product quality, brand image, and brand prestige can trigger the interest to buy back. This study used primary data sources (first source) with communication techniques and distributed questionnaires to 105 respondents, ie consumers who use OPPO smartphones. Sampling in this research using non probability sampling with judgment sampling technique. Techniques used in the development and testing of models and data processing is a model of structural equations using WarpPLS 4.0 program. And the results obtained in this study indicate that product quality, brand image, and brand prestige have a positive and significant effect on the interest of buy back on OPPO Smartphone product.Â Keywords: Product Quality, Brand Image, Brand Prestige, Buying Interest